1999
DOI: 10.1038/sj.bjc.6690178
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal lymph node metastasis model by orthotopic intrapulmonary implantation of Lewis lung carcinoma cells in mice

Abstract: Lung neoplasm, in place of gastric cancer, is the major cause of cancer mortality in Japan as well as in the USA (Travis et al, 1995). Despite the advances in diagnostic techniques for the early detection of lung cancer and the significant improvement in surgical procedures, the survival rate of lung cancer patients is poor even in the early stages of cancer as compared to the other malignant neoplasms. From a clinical point of view, one of the most troublesome impediments for treatment of lung cancer is the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 17 publications
1
71
0
Order By: Relevance
“…11 In brief, the left chest of anesthetized mice was incised 5 mm, and 20 ll aliquots of an LLC suspension (2 3 10 3 cells) admixed with 20 lg of Matrigel TM basement membrane matrix (BD Biosciences, San Jose, CA) were injected into the left lung parenchyma through the intercostal space. Mice were killed 15 days after implantation, and the weight of the tumors was measured.…”
Section: Tumor Proliferation In Vivomentioning
confidence: 99%
“…11 In brief, the left chest of anesthetized mice was incised 5 mm, and 20 ll aliquots of an LLC suspension (2 3 10 3 cells) admixed with 20 lg of Matrigel TM basement membrane matrix (BD Biosciences, San Jose, CA) were injected into the left lung parenchyma through the intercostal space. Mice were killed 15 days after implantation, and the weight of the tumors was measured.…”
Section: Tumor Proliferation In Vivomentioning
confidence: 99%
“…10,11 Other orthotopic athymic mouse models have also been reported for human cancers such as colon, pancreas, lung, stomach, liver, kidney, ovary, prostate, urinary bladder, breast, and head and neck. [12][13][14][15][16][17][18][19][20][21] Thus, an orthotopic athymic animal model would seem to be the most useful for studying esophageal cancer cell invasion and metastasis. No such model, however, has previously been reported.…”
mentioning
confidence: 99%
“…Previous studies have showed that the biological behavior of cancer cells is influenced by the implantation organ (1), while properties of the immune system are also known to be different in each organ. A useful model for a solitary pulmonary tumor has previously been established by the intrapulmonary implantation of LLC cells in syngeneic immunocompetent mice (7,(19)(20)(21). This model has the advantage of being simple and easy regarding the implantation procedure with a small skin incision at a pre-determined site followed by direct puncturing through the intercostal space to the lung parenchyma, without thoracotomy or intubation.…”
Section: Discussionmentioning
confidence: 99%